One semester of speaking tasks – an experimental approach with low proficiency students - Andrew N. Williams; Yah Awg Nik (2013)
Although there are many students who enter Malaysian universities with a high level of proficiency in English (MUET Band 3 and above) there are many others who struggle to express themselves in English (MUET Band 1 and 2). What would happen if all their class time in the first semester was used for speaking tasks? This study tested the hypothesis that undergraduate students with low proficiency, (MUET Band 1 and 2), would make the most rapid progress in English if the guided learning time (tutorials and lectures) in the first semester is used entirely for speaking tasks. A class of 30 students was taught using all 42 hours of contact time for speaking tasks, with a control class taught ‘as normal.’ Proficiency in the four language skills were measured at the start and end of the semester.